Australian health and medical workers' concerns around providing care to people living with hepatitis B. (6th April 2021) - Cama, Elena; Brener, Loren; Broady, Timothy; Hopwood, Max; Treloar, Carla
Abstract: There is established literature on health workers' attitudes towards working with people living with stigmatised health conditions and behaviours, such as HIV, hepatitis C and injecting drug use. Less is known about health workers' attitudes and concerns around providing care to people living with hepatitis B virus (HBV), which is concerning as research indicates that negative attitudes may impact on the quality of care provided to these populations, with adverse health outcomes for clients. The aim of this paper is to examine health and medical workers' concerns about providing care to people living with HBV, and the factors that may influence these concerns. Australian health and medical workers ( n  = 551) completed an online survey measuring their concerns about providing care to people living with HBV, stigmatising attitudes towards this group, perceived comfort of themselves and colleagues in providing care towards clients with HBV, and witnessing their colleagues behaviour in a discriminatory way towards clients with HBV. Multiple regression was used to ascertain factors predictive of health workers' concerns about working with clients with HBV. Results showed that older participants and those who had spent less time working in the health and medical field had greater concerns about caring for people living with HBV. Workers who did not know someone living with HBV, who were less comfortable around clients with HBV, who perceived their colleagues to be less comfortable working with clients with HBV, and who had more negative attitudes towards this group also had greater concerns around providing care to people living with HBV. Efforts should be made to improve health and medical workers' attitudes towards working with people with HBV. This may also improve workers' level of comfort with people with HBV and reduce the reported reticence they have towards working with this client group.